2021
DOI: 10.1007/s11419-020-00567-2
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between two different dried blood substrates in determination of psychoactive substances in postmortem samples

Abstract: Purpose Whatman™ 903 cards represent a valid type of support for collection, storage, and analysis of dried blood spots (DBS). Whatman™ FTA (Flinders Technology Associates) are a type of cards soaked in chemicals that cause denaturation of proteins, while preserving DNA and ensuring the safe handling of DBS; to date, these cards are still rarely employed in forensic toxicology. The aim of this study was to analyze several psychoactive substances on not-dried blood on the two different cards and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Recovery was evaluated at different sonication times (5,10,15,20,25 and 30 min). Fifteen minutes was considered as the best choice in terms of time saving and recovery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recovery was evaluated at different sonication times (5,10,15,20,25 and 30 min). Fifteen minutes was considered as the best choice in terms of time saving and recovery.…”
Section: Resultsmentioning
confidence: 99%
“…Since the 1950’s, several methods have been developed and validated for dried blood spots [ 1 , 2 , 3 , 4 , 5 , 6 ]. Among DMS, dried urine spots (DUS) have successfully been used for several analytical purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional methods of DNA extraction with phenol-chloroform, spin-columns, and magnetic beads can be time-consuming and expensive and need to be performed by trained personnel in a laboratory setting . Dried blood spot (DBS) samples, such as FTA Whatman and plasma separation cards, are newer low-cost alternatives where dried lysis and storage reagents on paper are activated upon sample spotting, thus eliminating the cell lysis step and simplifying sample preparation as well as improving sample storage and transportation for RLS. The cards allow between 40 and 140 μL volume of blood per spot; however, previous reports have shown that volumes of 50–100 μL could lead to inaccurate detection of viral pathogens and so larger sample volumes might be required to ensure optimal performance. Moreover, the uncontrolled flow of blood through the paper can cause the heterogeneous distribution of analytes within the sample spot, leading to variable results obtained from punching different areas of the DBS card. , The NA extraction protocol using these cards requires multiple washing steps to remove inhibitors prior to amplification. , A simpler method involves the addition of prelysed blood to a Whatman No. 1 filter paper disk, which, after a washing step, is added directly to the polymerase chain reaction (PCR) mix for amplification without removing the disk .…”
Section: Microfluidic Devices For Sample Preparation Of Undiluted Who...mentioning
confidence: 99%
“…The vast majority of these drugs have a short half-life, but DBS has a stabilization effect on them so they can endure for a longer period [7]. It is also worth mentioning that a recent study by Moretti et al describes a successful analysis of a few psychoactive substances and their metabolites in postmortem blood [12]. However, research conducted by Patteet et al also confirmed that DBS is vital in therapeutic drug monitoring of antipsychotics, but it excluded olanzapine and N-desmethylolanzapine [13].…”
Section: Substances Of Abuse Markermentioning
confidence: 99%